Letters of a woman homesteader - Stewart, Elinore Pruitt (Open Road Integrated Media, 2020)
This "warmly delightful, vigorously affirmative" memoir of a woman homesteader in early twentieth-century Wyoming inspired the acclaimed film Heartland (The Wall Street Journal). In 1909, Elinore Pruitt answered an ad in the Denver Post to become Henry Clyde Stewart's housekeeper on his homestead outside Burntfork, Wyoming. Elinore soon fell in love with the land's vast, untamed beauty, and filed a claim for her own adjoining property under the Homestead Act. Over the next five years, she not only made a home for herself, but traveled extensively across the state, befriending every neighbor within a hundred miles. Through it all'weddings and births, illnesses and snowstorms, changing seasons and changing times'Elinore maintained correspondence with her former employer Juliet Coney in Denver, Colorado. In vivid detail and with lively prose, Elinore told Juliet of life as a woman in the American West. First published in the Atlantic Monthly, these letters made their author an American icon of her time. "Full of the tang of the prairies and of a delightful personality." 'The New York Times.